Uniqueness of elastic continuation in a semilinear elastic body - Ang, Dang Dinh; Dung, Nguyen; Huy, Nguyen Vu; Trong, Dang Duc (Vietnam Journal of Mechanics, 2003)
The authors prove a theorem on uniqueness of elastic continuation in a nonhomogeneous elastic solid with a displacement-dependent tension modulus, generalizing an earlier result by Ang, Ikehata, Trong and Yamamoto for a nonhomogeneous linear elastic solid.